Optimum Allocation of Super Stores in Dhaka City: An Application of Geographic Information System (GIS) and Heuristic Model - Md Mostahidur Rahman; Susmita Chakraborty (Journal of Bangladesh Institute of Planners, 2010)
For well functioning of a city, it is very important to ensure the optimum location of different public facilities. Super markets follow the theme of arranging all kinds of products under one roof for the consumers. The objective of this study is to determine the availability of super stores and analysis of locations of super stores in Dhaka City. The study explores the optimum location of super stores to minimize inconveniences faced by the residents to access super stores. Optimal locations of super stores are identified by using Heuristic Model. In the study area, super stores have grown haphazardly and people are not getting their desired services. On the other hand, owners of super stores failed to earn their preferred profit. The study integrated GIS methods and Heuristic Model to determine demand wise distribution of super stores in the city. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 153-158